2014
DOI: 10.1002/wsbm.1275
|View full text |Cite
|
Sign up to set email alerts
|

Cell mechanics: principles, practices, and prospects

Abstract: Cells generate and sustain mechanical forces within their environment as part of their normal physiology. They are active materials that can detect mechanical stimulation by the activation of mechanosensitive signaling pathways, and respond to physical cues through cytoskeletal re-organization and force generation. Genetic mutations and pathogens that disrupt the cytoskeletal architecture can result in changes to cell mechanical properties such as elasticity, adhesiveness, and viscosity. On the other hand, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
221
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(244 citation statements)
references
References 121 publications
1
221
0
6
Order By: Relevance
“…Yet how actomyosin-generated forces coordinate with geometric and mechanical parameters (such as the constriction size and the stiffness of the extracellular matrix and the nucleus) to modulate the nuclear morphology during cell passage through small openings remains poorly understood. Furthermore, despite the development of a variety of approaches that model the mechanics of the whole cell (16)(17)(18), a mechanistic model to assess the ability of cells to pass through small constrictions and the role of the nucleus and other biophysical parameters is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Yet how actomyosin-generated forces coordinate with geometric and mechanical parameters (such as the constriction size and the stiffness of the extracellular matrix and the nucleus) to modulate the nuclear morphology during cell passage through small openings remains poorly understood. Furthermore, despite the development of a variety of approaches that model the mechanics of the whole cell (16)(17)(18), a mechanistic model to assess the ability of cells to pass through small constrictions and the role of the nucleus and other biophysical parameters is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Authors consider the cell as a separate phase material, which consist 60% of water. They suggested that this component acts as a determining factor of the cytoskeleton behavior [2]. This assumption is not new, it had been used in earlier publications, where interactions of water and proteins were analyzed [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…According to this model, cytoplasm is a flexible and durable mesh which is sensitive to pressure changes inside the cell. Viscoelastic properties of the biological cell depends on the flow of the not-cellular fluid in response to mechanical impact [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are a few studies of cell nanostructure under endotoxemia. Modern biomedical technologies used for this purpose offer new opportunities to reveal pathophysiological regularities of the disease presentation in different groups of patients [3].…”
mentioning
confidence: 99%